Thermostable Lactonases Inhibit IPseudomonas aeruginosa/I Biofilm: Effect In Vitro and in IDrosophila melanogaster/I Model of Chronic Infection - Porzio, Elena; Andrenacci, Davide; Manco, Giuseppe (International journal of molecular sciences, 2023)
Pseudomonas aeruginosa is one of the six antimicrobial-resistant pathogens known as “ESKAPE” that represent a global threat to human health and are considered priority targets for the development of novel antimicrobials and alternative therapeutics. The virulence of P. aeruginosa is regulated by a four-chemicals communication system termed quorum sensing (QS), and one main class of QS signals is termed acylhomoserine lactones (acyl-HSLs), which includes 3-Oxo-dodecanoil homoserine lactone (3-Oxo-C12-HSL), which regulates the expression of genes implicated in virulence and biofilm formation. Lactonases, like Paraoxonase 2 (PON2) from humans and the phosphotriesterase-like lactonases (PLLs) from thermostable microorganisms, are able to hydrolyze acyl-HSLs. In this work, we explored in vitro and in an animal model the effect of some lactonases on the production of Pseudomonas virulence factors. This study presents a model of chronic infection in which bacteria were administered by feeding, and Drosophila adults were treated with enzymes and the antibiotic tobramycin, alone or in combination. In vitro, we observed significant effects of lactonases on biofilm formation as well as effects on bacterial motility and the expression of virulence factors. The treatment in vivo by feeding with the lactonase SacPox allowed us to significantly increase the biocidal effect of tobramycin in chronic infection.